Development of a Framework for More Effective Implementation of Total Quality Management Principles in Apparel Manufacturing - Setu, S.M. Rashadur Rahaman; Hossain, Md. Helal; Hossain, Md. Tanjim; Sarkar, Jahid (European Scientific Journal, ESJ, 2016)
The purpose of this paper is to develop a model or framework of total quality management (TQM) implementation in Textile and RMG industry. Textile and RMG Industry is an important sector for Bangladesh in terms of industrial expansion of the country, earning foreign currency and creating job opportunities. However, it faces subtle problems due to labor unrest, political instability and owner’s ignorance. TQM is an approach that focuses on customer satisfaction. Therefore, implementation of TQM is a challenging task. Through a self-administrative survey from 50 Industries of textile and RMG industry in Bangladesh data have been collected. This paper identifies ten key factors of TQM implementation in the Textile and RMG Industry in Bangladesh. These are Leadership, Communication, Strategic Quality Planning, Training, Customer Satisfaction, Continuous Improvement, Employee Involvement & Satisfaction, Culture, Supplier Satisfaction and Teamwork.